Pediatric Patients Who Underwent Elbow Arthroscopy Had an 86% Return-to-Sport Rate, a 12% Reoperation Rate, and a 3.7% Complication Rate - Nick F.J. Hilgersom, M.D; Myrthe Nagel, M.D; Bertram The, M.D., Ph.D; Michel P.J. van den Bekerom, M.D., Ph.D; Denise Eygendaal, M.D., Ph.D (Elsevier, 2024)
Purpose: To assess the applicability and safety of elbow arthroscopy in the pediatric population at our institution by analyzing the indications and complications in a large pediatric patient series. Methods: We retrospectively identified all patients who underwent elbow arthroscopy at age 18 years or younger from 2006 to 2017 performed by a single fellowship-trained surgeon. The exclusion criteria were follow-up shorter than 8 weeks and open surgical procedures (not fully arthroscopic). Medical records were reviewed for baseline characteristics, indications for elbow arthroscopy, range of motion, complications, and reoperations. Results: In total, 191 patients (64 boys and 127 girls) were included, with a median age of 15.5 years (interquartile range, 14.0-16.7 years). Indications for arthroscopic surgery were grouped into treatment of osteochondritis dissecans (60%), debridement for bony or soft-tissue pathology (35%), contracture release (3%), and diagnostic arthroscopy (3%). The complication rate was 3.7%, including 4 minor complications (3 superficial wound problems and 1 case of transient ulnar neuropathy) and 3 major complications (1 case of manipulation under anesthesia for stiffness, 1 deep infection, and 1 [unplanned] reoperation for persistent locking within 1 year of the index procedure). Subsequent surgery was required in 23 patients (12%) because of newly developed, persisting or recurring elbow problems. Of the patients, 86% were able to return to sports. Conclusions: Pediatric elbow arthroscopy performed by an experienced surgeon using a standardized technique for a wide variety of elbow conditions has an acceptable complication rate that is similar to rates in the previously published literature on elbow arthroscopy in the pediatric and adult populations; however, a significant proportion of patients needed subsequent surgery in the following years. Level of Evidence: Level IV, therapeutic case series.